2022
DOI: 10.3389/fmats.2021.796474
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Air Plasma Pretreatments on Mechanical Properties in Metal-Reinforced Laminated Wood

Abstract: The use of wood-based materials in building and construction is constantly increasing as environmental aspects and sustainability gain importance. For structural applications, however, there are many examples where hybrid material systems are needed to fulfil the specific mechanical requirements of the individual application. In particular, metal reinforcements are a common solution to enhance the mechanical properties of a wooden structural element. Metal-reinforced wood components further help to reduce cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Further studies showed an even larger increase in shear strength and bending strength, as well as an impact on the modulus of elasticity of the compound. Notably, the PVAc bonds of plasma-treated substrates outperformed state-of-the-art adhesives for such composites as epoxy and polyurethane [15]. However, the question remains open: what modifications occur on the surfaces due to the plasma treatment, i.e., what interactions at the molecular level lead to this significant increase in shear strength?…”
Section: Introductionmentioning
confidence: 99%
“…Further studies showed an even larger increase in shear strength and bending strength, as well as an impact on the modulus of elasticity of the compound. Notably, the PVAc bonds of plasma-treated substrates outperformed state-of-the-art adhesives for such composites as epoxy and polyurethane [15]. However, the question remains open: what modifications occur on the surfaces due to the plasma treatment, i.e., what interactions at the molecular level lead to this significant increase in shear strength?…”
Section: Introductionmentioning
confidence: 99%